Successful treatment of residual pituitary adenoma in persistent acromegaly following localisation by 11C-methionine PET co-registered with MRI. Issue 5 (November 2016) - Koulouri, Olympia; Kandasamy, Narayanan; Hoole, Andrew C; Gillett, Daniel; Heard, Sarah; Powlson, Andrew S; O'Donovan, Dominic G; Annamalai, Anand K; Simpson, Helen L; Akker, Scott A; Aylwin, Simon J B; Brooke, Antonia; et al.
Abstract : Objective: To determine if functional imaging using 11 C-methionine positron emission tomography co-registered with 3D gradient echo MRI (Met-PET/MRI), can identify sites of residual active tumour in treated acromegaly, and discriminate these from post-treatment change, to allow further targeted treatment. Design/methods: Twenty-six patients with persistent acromegaly after previous treatment, in whom MRI appearances were considered indeterminate, were referred to our centre for further evaluation over a 4.5-year period. Met-PET/MRI was performed in each case, and findings were used to decide regarding adjunctive therapy. Four patients with clinical and biochemical remission after transsphenoidal surgery (TSS), but in whom residual tumour was suspected on post-operative MRI, were also studied. Results: Met-PET/MRI demonstrated tracer uptake only within the normal gland in the four patients who had achieved complete remission after primary surgery. In contrast, in 26 patients with active acromegaly, Met-PET/MRI localised sites of abnormal tracer uptake in all but one case. Based on these findings, fourteen subjects underwent endoscopic TSS, leading to a marked improvement in ( n = 7), or complete resolution of ( n = 7), residual acromegaly. One patient received stereotactic radiosurgery and two patients with cavernous sinus invasion were treated with image-guided fractionated radiotherapy, with good disease control. Three subjects await further intervention. Five patients chose to receive adjunctive medical therapy. Only one patient developed additional pituitary deficits after Met-PET/MRI-guided TSS. Conclusions: In patients with persistent acromegaly after primary therapy, Met-PET/MRI can help identify the site(s) of residual pituitary adenoma when MRI appearances are inconclusive and direct further targeted intervention (surgery or radiotherapy).